7.5k views
4 votes
HELP HELP HELP PLEASEEEEEEE

HELP HELP HELP PLEASEEEEEEE-example-1

1 Answer

1 vote

Explanation:

there is nothing special about this. no need to panic.

any arithmetic operation with functions means that we do these operations with the expressions of the functions. that's all.

(s.t)(x)

just means (s×t)(x) = (4x + 4)(5x) = 20x² + 20x

(s + t)(x) = (4x + 4) + (5x) = 9x + 4

(s - t)(x) = (4x + 4) - (5x) = -x + 4

so, (s - t)(1) = -1 + 4 = 3

User Fyr
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.